Factores asociados al síndrome de fragilidad en los adultos mayores residentes del barrio San Cayetano de la ciudad de Loja - Saritama Carrión, Gloria Stefany (2023)
Frailty constitutes a geriatric syndrome, which represents a public health problem in Ecuador. With aging, the functional deterioration of the individual increases and so does the vulnerability to suffering adverse events; its main complications are disability and mortality. The general objective was to determine the incidence of Frailty Syndrome in the elderly resident of the San Cayetano neighborhood of the city of Loja. In this context, the first specific objective was to identify the frailty syndrome using the Fried criteria. The second objective was to assess the functional factors associated with the frailty syndrome, through the variables: falls, cognitive impairment and depression. The third was to establish the relationship between the frailty syndrome and the associated functional factors. It was a quantitative, observational, analytical, cross-sectional study developed in 197 adults over 65 years of age. Through simple probabilistic sampling and prior application of informed consent, the incidence of frailty syndrome was evaluated, obtaining as results the predominance of pre-frailty with 46.19%, and 37.56% presented frailty. Regarding the functional factors associated with this syndrome, the risk rate of falls was 58.89% with a high risk. Regarding mental status, it was recorded that 40.61% of the population presented mild cognitive impairment and only 1.02% registered severe cognitive impairment, predominating in the female sex and compared to the depression index, 46.70% presented moderate depression. There was a statistically significant relationship between the frailty syndrome and associated functional factors with a value of p< 0.05, concluding that the frailty syndrome influences the level of cognitive impairment and depression.